The Impact of Digital Transformation on Organizational Performance in Japan - Nakamura, Takuya (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to investigate the impact of digital transformation on organizational performance in Japan. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Transformative impact of digital transformation on organizational performance in Japan. Key findings reveal significant improvements in efficiency and productivity through automation and AI integration, alongside enhanced customer experiences through personalized digital interactions. Innovation has been accelerated by technologies like IoT and big data analytics, enabling agile responses to market demands. Despite these advancements, challenges such as legacy system integration and cybersecurity threats persist, requiring proactive leadership and workforce upskilling. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV), dynamic capabilities theory& technology acceptance model (TAM) may be used to anchor future studies on the digital transformation on organizational performance in Japan. Organizations should develop comprehensive digital transformation roadmaps that align with their strategic goals and operational needs. Policymakers should collaborate with industry stakeholders to develop flexible regulatory frameworks that promote innovation while safeguarding data privacy and security.